2015
DOI: 10.1021/jacs.5b01763
|View full text |Cite
|
Sign up to set email alerts
|

Hückel Theory and Optical Activity

Abstract: Optical rotations and rotatory strengths are calculated for achiral, conjugated hydrocarbons with the aim of determining to what extent the sum-over-π → π* rotatory strengths are sufficient to account for nonresonant optical activity. The separability of σ and π electrons might provide a short cut to the interpretation of chiroptical structure-property relations in some cases. It is shown that by restricting the analyses to planar, C(2v)-symmetric π-systems and their one electron HOMO-LUMO excitations, an intu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…However, chiral molecules have twisted wave functions that are hard to reckon in the mind's eye. Recently, we have shown that planar π‐conjugated molecules with symmetries supporting optical activity when oriented, facilitate structure‐property correlations because their π electronic structure can be intuitive . Once the wave functions of optically active compounds can be rendered in a plane, in our experience, the mechanism of optical activity becomes transparent.…”
Section: Introductionmentioning
confidence: 92%
“…However, chiral molecules have twisted wave functions that are hard to reckon in the mind's eye. Recently, we have shown that planar π‐conjugated molecules with symmetries supporting optical activity when oriented, facilitate structure‐property correlations because their π electronic structure can be intuitive . Once the wave functions of optically active compounds can be rendered in a plane, in our experience, the mechanism of optical activity becomes transparent.…”
Section: Introductionmentioning
confidence: 92%
“…The electronic transition involves donor orbitals of highest occupied molecular orbital (HOMO) – 1 or HOMO type, whereas acceptor orbitals are lowest unoccupied molecular orbital (LUMO), LUMO + 1, or LUMO + 2. In most clusters, a significant number of transitions are involved, with small individual contributions, a feature typical of realistic complex systems. , Exceptions are the Au 3 Ag 3 and Au 3 Cu 3 clusters. Finally, only a limited number of electronic transitions lies below 3 eV, mostly with low intensities ( f < 0.1).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The third Cartesian direction is about zero. Interpreting this tensor in terms of a small number of excited states is difficult because unlike simple hydrocarbons investigated previously, 96,97 a great number of states contribute to the long wavelength value of benzil. For instance, the g xx tensor element for one molecule which has a value of 9.8 bohr 4 , requires summing the contributions from 100 excited states at a minimum.…”
Section: ■ Introductionmentioning
confidence: 98%